ARTIFICIAL SLIDING MODE CONTROL OF AN ACTIVE ELECTRO-MECHANICAL HALF-VEHICULAR SUSPENSION SYSTEM WITH ACTUATORS AND ANN-BASED CONTROLLER - Muhammad Waqas; Muhammad Iftikhar Khan; Ali Murtaza; Bilal Ahmed; Manahil Iqra; Bilal Ur Rehman; Kifayat Ullah; Muhammad Farooq (Spectrum of Engineering Sciences, 2025)
Suspension systems play a critical role in determining the comfort levels of passengers and vehicle stability, especially in dynamic road conditions. This paper describes an implemented electro-mechanical half-vehicle suspension system, initially using a basic model of the suspension. The actuators are then incorporated into the model to enhance the system’s performance. Subsequently, an ANN controller is used to enhance further the system’s response to road disturbances in the real world. These findings reveal that ride comfort, vehicle handling, and system ruggedness have improved significantly, and the active suspension system is slightly better compared to conventional passive suspension systems. Specifically, the addition of actuators and an ANN controller results in reduced overshoot, increased fault tolerance, and shorter settling times when exposed to road disturbances at various speeds.